A few problems on the enforcement of acts of the European Court of Human Rights - D. T. Karamanukyan (Сибирское юридическое обозрение, 2014)
The article is dedicated to the urgent problem of human rights acts law enforcement of the European Court by the public authorities of the Russian Federation. The author brings to attention the specifics of law enforcement acts execution of the European Court in Human Rights relating to the implementation of such measures, as individual and general ones. Summarizing this doctrinal analysis, the author offers a number of ways to improve the existing process of the European Court acts law enforcement in the Russian Federation.